Bedside shift report: Nurses opinions based on their experiences. Issue 3 (30th December 2020) - Jimmerson, Joseph; Wright, Patricia; Cowan, Patricia A.; King‐Jones, Tammy; Beverly, Claudia J.; Curran, Geoffrey
Abstract: Background: Nurse bedside shift report (BSR) improves satisfaction, quality and safety. Yet, postimplementation adoption rates remain low in hospitals where BSR has been introduced. Further research is needed to understand what content is most appropriate to discuss during BSR and what facilitators are from the clinical nurses' perspective. Aims: Identify and describe acute care clinical nurses' and nursing supervisors' experiences and opinions regarding: process of BSR, appropriate content for BSR and barriers and facilitators related to implementation of BSR. Design: A phenomenological qualitative study was conducted at an acute care 500 bed, not‐for‐profit academic medical centre located in the southern United States. Methods: Clinical nurses ( N  = 22) and nursing supervisors ( N  = 12) from every inpatient division were recruited and interviewed. The data were analysed for relationships, similarities and differences. Themes were then identified by two independent researchers. Results: Five themes were identified: (a) time constraints and clinical nurse's workflow must be taken into consideration; (b) a modified approach is necessary; (c) process and specific critical content should be individualized so that it is meaningful for all parties involved; (d) specific critical content that should be discussed outside the patient's room; and (e) specific critical content that should be discussed inside the patient's room. Conclusions: One way to minimize interruptions is to conduct BSR using a modified approach, where a portion of the hand‐off occurs inside and outside the patient's room. In addition, this study identified the nurses' preferred location where specific critical topics should be discussed. Relevance to clinical practice: Results from this study should be used to inform the practice BSR so the desired outcomes of patient and family satisfaction, nursing quality and patient safety can be realized. This study should influence future research aimed at identifying strategies for successful implementation and sustained use of BSR. The COREQ checklist was used to write manuscript.